The Effect Of The Method Of Analyzing The Error And His Knowledge In Learning The Lift Of Kidnapping Among Students Of The Faculty Of Physical Education And Sports Sciences By Weightlifting - Ali Lateef, Nibras (International Journal of Psychosocial Rehabilitation, 2020)
In the shadow of great scientific and cognitive progress in various fields of life, information became widespread at the time of its birth, and the expansion of the field for anyone with a bright idea and a good opinion through the Internet to be the subject of research in an international seminar in this scene, all teachers and professors in universities should benefit from this reality to promote the educational process at various levels of its educational institutions. At the forefront of the field of physical education and sports to improve the level of physical education lesson from kindergarten to university (our research stage), especially in the field of the impact of error analysis and knowledge in learning to raise kidnapping to work to involve the learner and highlight his positive role and thus increase the motivation of the learner, including analysis of error